2011
DOI: 10.1111/j.1365-3059.2010.02414.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and diseases of food crops

Abstract: Despite complex regional patterns of projected climate change, significant decreases in food crop yields have been predicted using the 'worst case' CO 2 emission scenario (A1FI) of the Intergovernmental Panel on Climate Change. Overall, climate change is predicted to have a progressively negative effect on the yield of food crops, particularly in the absence of efforts to mitigate global CO 2 emissions. As with all species, plant pathogens will have varying responses to climate change. Whilst the life cycle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
165
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(183 citation statements)
references
References 66 publications
0
165
0
6
Order By: Relevance
“…However, it is widely considered to also affect plant morphology, canopy structure, and hence micro-climate and the resident micro-floral populations in such environments (Eastburn et al 2011). Thus far, different studies have given conflicting results showing that elevated CO 2 levels may have negative, neutral, or positive effects on fungal growth (Luck et al 2011). Indeed, the Climapest project, covering 20 different crops throughout Brazil, concluded that climate change can "decrease, increase, or have no impact on plant diseases, pests, or weeds depending on the region and the time period" (http://www.…”
Section: Pest Evolution Under Climate Changementioning
confidence: 96%
“…However, it is widely considered to also affect plant morphology, canopy structure, and hence micro-climate and the resident micro-floral populations in such environments (Eastburn et al 2011). Thus far, different studies have given conflicting results showing that elevated CO 2 levels may have negative, neutral, or positive effects on fungal growth (Luck et al 2011). Indeed, the Climapest project, covering 20 different crops throughout Brazil, concluded that climate change can "decrease, increase, or have no impact on plant diseases, pests, or weeds depending on the region and the time period" (http://www.…”
Section: Pest Evolution Under Climate Changementioning
confidence: 96%
“…Hijmans (2000) has predicted that for each 1 °C warming, late blight would occur 4 to 7 days earlier, and the susceptibility period is extended by 10 to 20 days (Kaukoranta, 1996). In India, late blight now appears earlier in the northern part (November) and later in eastern parts (February) and within a higher temperature range of 14-27.5 °C than at 10-25 °C which used to occur in the past (Luck et al, 2011).…”
Section: The Impact Of Elevated Temperature On the Biology Of Insect mentioning
confidence: 99%
“…In north-western plains of India, late blight of potato used to occur in mild to moderate form only once in 4 to 5 years, but more recently as a result of climate warming, it is occurring every 2 years (Luck et al, 2011). Climate warming extends the period of activity of the late blight pathogen (Luck, 2011).…”
Section: The Impact Of Elevated Temperature On the Biology Of Insect mentioning
confidence: 99%
See 1 more Smart Citation
“…Above-and belowground biomass accumulation exhibits strong and consistent increases under elevated CO 2 (Eastburn et al, 2011). However, the effects on plant diseases may differ according to the pathogen, the host, the environmental conditions, and the methodology used in the studies (Luck et al, 2011).…”
Section: Crescimento De Plantas E Severidade Da Mancha Foliar Em Eucamentioning
confidence: 99%